Colour vision of diabetics. Issue 7 (July 1985) - Green, F D; Ghafour, I M; Allan, D; Barrie, T; McClure, E; Foulds, W S
Abstract : The Farnsworth-Munsell 100-hue test has been assessed as a screening test for the detection of diabetic retinopathy likely to benefit from laser photocoagulation therapy. Two hundred and thirty-two diabetic eyes of 126 patients were tested. The results were assessed both for total error score relative to age and for the presence of polarity. Although the incidence of abnormal colour discrimination was found to correlate with the severity of retinopathy, the test was not sufficiently selective to be of value as a screening test in the detection of retinopathy requiring treatment.